Vacuum stability in B-LSSM. (18th June 2021) - Yan, Ben; Feng, Tai-Fu; Zhao, Shu-Min; Zhang, Hai-Bin; Yang, Jin-Lei
Abstract: B-L supersymmetric standard model (B-LSSM) is the U (1) extension of the minimal supersymmetric standard model (MSSM). Comparing with MSSM, B-LSSM has several advantages. The vacuum stability is a very important problem. The Higgs super-fields in B-LSSM are more than those in the MSSM. It is interesting to study the vacuum stability in the B-LSSM. The one-loop effective potential and two-loop renormalization group equations are taken into account. In the numerical calculation, we obtain useful results. They can confine the parameter space of the B-LSSM and make clear behavior of the effective potential with running scale. It is in favour of detecting new physics beyond the standard model.